Populism Versus Racism in Trump’s Campaigns: A Thematic Analysis of ‘Make America Great Again’ Rhetoric - FATMI, Rim; GUELLIL, Assia (Faculty of Letters and Foreign Languages Department of English, 2025)
Trump’s 2016 presidential campaign incorporated populism, racism, and the “Make America Great Again” (MAGA) rhetoric. These elements mobilized white voters sharing cultural and economic anxieties by arousing feelings of nostalgia to an idealized past of America. Their sense of grievance and discontent is expressed through racial resentment. Considering the above statement, it is necessary to investigate the reason behind adopting this racialized political strategy by Trump. The present work aims at examining how polarisation and exclusion are entrenched by populist messages through the ‘MAGA’ rhetoric. To achieve this objective, a qualitative approach is adopted for a thematic analysis of the “MAGA” rhetoric to capture how it constructs racialized and populist narratives. The findings revealed that the “MAGA” rhetoric promotes exclusion and discrimination. It shapes the nation ethnically by defining ‘white’ citizens as dominants while minorities and immigrants are portrayed as threats which creates hostility, and legitimizes racism. The “MAGA” rhetoric is a driver of populist belief